Analisis Aspek Keterampilan Proses Sains Dasar Pada Buku Teks IPA Siswa Sekolah Dasar Kelas VI - Darmayanti, N.W.S; Wijaya, I.K.M. Wisnu Budi; Sanjayanti, N.P.A.H; Janawati, Dsk. Pt. Anom (Universitas Nusantara PGRI Kediri, 2021)
This study aims to describe the aspects of basic science process skills in the 6th grade Bupena Elementary School (SD) science textbook. This research is a descriptive study with a qualitative approach. The Bupena SD class VI A science textbook is the source of the data in the study. The instrument used in this study was a checklist or a suitable list. The data collection technique was used documentation, study, where the data were obtained from examining documents in the form of a Bupena SD science textbook for grade VI A. The process of collecting data was by providing a checklist on each aspect. Basic science process skills contained in each theme of the Bupena science textbook. The data processing technique was carried out by calculating the percentage of the 6th grade Bupena science textbook that facilitates basic science process skills. The results showed that the percentage of aspects of basic science process skills in the Bupena theme 1 science textbook were 83% with the very facilitating category. Furthermore, theme 2, the percentage of content is 67%, with the category of sufficiently facilitating. The percentage of content in theme 3 is 83%. However, overall the Bupena science textbook has presented material that facilitates basic science process skills. The number of activities that present or contain aspects of basic science process skills in the Bupena IPA textbook varies, with the highest number of activities in the observing aspect, namely 19 activities. The measuring aspect has not been included in the Bupena science textbook because there is no science material related to measuring activities.